Studi Keterkaitan Negara Hukum Dan Kekuasaan Dalam Perspektif Politik Hukum - Nickolaz Boy Regawoge; Siti Aminah Mega Putri; Maria Ulfa; Parningotan Malau (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
Power is closely related to law because power is not only concerned with the instruments of lawmaking, but also includes law enforcement. The synergistic character of law and power, especially in terms of the legality of power, is explained by Mochtar Kusumaatmadja with one phrase, "Law without power is a dream and power without law is despotism." This synergy between law and power can be seen as the division of power known as the Trias Politica principle. Power consisting of legislative, executive, and judicial institutions is regulated by the 1945 Constitution as the highest source of law in Indonesia. This paper uses a juridical-normative study research method with a literature review in the form of secondary data, namely journals and books resulting from previous research. The results of this study indicate that law and power are closely related. Law and power run side by side and cannot be separated from each other. The essence of power is the ability of a person to impose their will on others. Law exists because of legitimate power. It is legitimate power that creates law. This means that law and power are complementary to each other.